Personality Type, Adversity Quotient, and Challenges of Student-Athletes in a Catholic University - Brendly Ann C. Mateo; Chris Feli Joy P. Tajonera (Philippine Social Science Journal, 2020)
Student-athletes are a unique student population requiring support for academic, personal, and athletic needs and issues. As the student-athletes deal with wins and losses, their ability to cope with failures will greatly help.  However, the means of how to address these difficulties differ in any way. Hence, this study aspires to explore the personality type, adversity quotient, and challenges student-athletes face in a Catholic university during the academic year 2019-2020. Likewise, it explores the differences between the respondents' demographics and their personality type and adversity quotient. Also, it determines whether a correlation exists between personality type and the adversity quotient of student-athletes. Moreover, it delves into the challenges encountered by student-athletes.